Aging and post-polymerization effects on conversion degree and properties of additive splint materials - Leandro Ruivo de SANTIS; Lucas Silveira FERNANDES; Mayra Torres VASQUES; Nataly Rabelo Mina ZAMBRANA; Ítallo Emídio Lira VIANA; Taís Scaramucci FORLIN; Guilherme de Siqueira Ferreira Anzaloni SAAVEDRA; Carlos Eduardo FRANCCI (Brazilian Oral Research)
Abstract The study objective was to analyze dimensional change, flexural strength, surface hardness, wear profile, and conversion degree of different additive splint materials under various post-polymerization conditions of time and artificial aging. Two additive manufacturing systems (Cara Print 4.0, Dima Print Ortho, Kulzer; SprintRay Pro, SprintRay Splint, SprintRay), and a thermally activated resin control (Clássico) were evaluated in artificial aging (deionized water or saliva; 28 or 84 days at 37°C), with recommended or doubled post-polymerization cycles. Dimensional change (surface metrology), flexural strength (ISO 20795-1:2013), fractography (SEM), Knoop hardness, two-body wear profilometry (150,000 cycles; 3mmØ; 20N; 2.1Hz), and conversion degree (FTIR spectroscopy) were assessed. Two-way ANOVA and post-hoc Tukey tests were used for parametric data, and Kruskal-Wallis and post-hoc Dunn tests, for non-parametric data (α = 0.05). Results indicated no statistically significant differences in dimensional change or flexural strength among the materials. Recommended post-polymerization cycles resulted in lower hardness for additive resins than the thermally activated control. Doubling post-polymerization time significantly increased flexural strength and hardness of Dima Print Ortho, but decreased flexural strength of SprintRay Splint, and did not affect wear resistance. Dima Print Ortho demonstrated the highest wear resistance. Artificial aging did not affect flexural strength, surface wear, or dimensional change, but negatively impacted the hardness of all materials except Dima Print Ortho. The conversion degree was unaffected by post-polymerization time, and no significant differences were found among the materials. Overall, additive materials exhibited mechanical and dimensional properties comparable to thermally activated resin, with doubling post-polymerization time positively influencing the properties.